Estimating the Impact of Uncertainty on a Deterministic Multiattribute Evaluation - Kirkwood, Craig W. (Management Science, 1992)
A method is presented to estimate the impact of uncertainty on the results of a multiattribute evaluation prior to conducting a complete probabilistic multiattribute utility analysis. The method assumes that a deterministic analysis has been completed using a weighted-additive multiattribute value (evaluation) function and that either an additive or multiplicative utility function is appropriate for the multiattribute utility analysis. An approximation procedure is developed to estimate whether uncertainty about attribute levels could change the deterministic evaluation results. An illustrative application investigates the accuracy of the procedure and its use to simplify analysis of the effects of uncertainty.